Physicochemical characteristics of struvite crystals formed in palm oil mill effluent anaerobic digester - Ngatiman, Muzammil; Jami, Mohammed Saedi; Abu Bakar, Mohd Rushdi; Subramaniam, Vijaya; Kheang, Loh Soh (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
The formation of struvite crystals in palm oil mill effluent (POME) occurs as early as in the secondary stage of POME treatment system. It continues to occur in the following tertiary treatment reducing the piping diameter thus affecting the efficiency of the treatment process. It is rarely being reported in scientific articles in the context of POME treatment in spite of its nature of being a common problem faced by the oil palm industry when it comes to the management of POME. This study aims at characterizing struvite crystals found in an anaerobic digester of a POME treatment facility in terms of their physical and chemical aspects. The composition, morphology and properties of these crystals were analyzed by energy dispersive spectroscopy (EDS), elemental analyzer, scanning electron microscopy (SEM) and x-ray diffraction (XRD). EDS discovered high phosphorous (P) content of 24.85 wt% and magnesium (Mg) content of 21.33 wt%. Elemental analysis also detected carbon (C), hydrogen (H), nitrogen (N) & sulfur (S) below 4 wt%. The sample used in this study was confirmed as struvite through XRD analysis where struvite mineral was detected as 94.8% of the total sample volume. Having an orthorhombic crystal system, struvite crystal from POME recorded a density of 1.701 g/cm3. This result indicates a high potential for struvite crystal from POME to be utilized as fertilizer. Its significant composition of phosphorous promises an alternative source to the ever increasing demand of phosphate as a source of fertilizer.